2021
DOI: 10.1111/jac.12485
|View full text |Cite
|
Sign up to set email alerts
|

Effects of two water regimes on morphological traits, nutritive value and physiology of three Bituminaria bituminosa varieties from the Canary Islands

Abstract: Morphological traits, nutritive values and physiological responses to two different water regimes of three Bituminaria bituminosa varieties: var. albomarginata, var. crassiuscula and var. bituminosa were evaluated in a greenhouse experiment. Two water regimes were imposed for 63 days; well‐watered (WW) plants and deficit‐watered (DW) plants, both starting from a high soil water content (dripping point). The three varieties showed similar aerial biomass reduction under reduced watering, 50% for var. albomargina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 63 publications
0
1
0
Order By: Relevance
“…Both of these outcomes pose an increased climate risk to the dairy and meat industries (Perera et al., 2020; Rojas‐Downing et al., 2017). Along with changes in pasture productivity, there are also potential shifts in the morphological traits and nutritional composition of pasture species that are likely to alter forage quality and digestibility (AbdElgawad et al., 2014; Fernández‐Habas et al., 2021; Herrero et al., 2015; Howden et al., 2008). In contrast to shifts in productivity, these changes and their consequences under future climate scenarios, such as warming and drought, are relatively understudied.…”
Section: Introductionmentioning
confidence: 99%
“…Both of these outcomes pose an increased climate risk to the dairy and meat industries (Perera et al., 2020; Rojas‐Downing et al., 2017). Along with changes in pasture productivity, there are also potential shifts in the morphological traits and nutritional composition of pasture species that are likely to alter forage quality and digestibility (AbdElgawad et al., 2014; Fernández‐Habas et al., 2021; Herrero et al., 2015; Howden et al., 2008). In contrast to shifts in productivity, these changes and their consequences under future climate scenarios, such as warming and drought, are relatively understudied.…”
Section: Introductionmentioning
confidence: 99%
“…B. bituminosa is a widely used forage species on the Canary Islands and accessions are therefore adapted to a huge gradient of rainfall. In studies, its adaptation to drought conditions has been confirmed along with high forage provision potential (e.g., Fernández‐Habas et al, 2021; Méndez et al, 1991). Depending on the variety, B. bituminosa exhibits both drought tolerance and cold tolerance.…”
Section: Methodsmentioning
confidence: 94%
“…Clay soil has two-fold the water content of loamy sand soil at saturation (Table 1). Fernández-Habas et al [18] pointed out that the root system development of B. bituminosa var albomarginata could be negatively affected by high soil water content in soils with elevated soil water retention capacity such as clay/silty soils, which could explain the reduction in thin root dry mass of plants grown in clay soil. Differences in soil P content could also affect root biomass [70,71].…”
Section: Effect Of Soil Typementioning
confidence: 99%
“…albomarginata from the Canary Islands, where it is known by the common name Tedera [14]. Previous research has demonstrated that this species is productive under very low rainfall (<200 mm), is highly drought-resistant [15][16][17], has good forage quality [18][19][20], and it is suitable for feeding livestock [14,[21][22][23]. Recently, an improved variety has been developed as a result of a collaborative breeding programme led by Australian and Spanish researchers [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation